XRCC5 as a risk gene for alcohol dependence: evidence from a genome-wide gene-set-based analysis and follow-up studies in Drosophila and humans - Juraeva, Dilafruz; Sommer, Wolfgang H.; Mann, Karl; Kiefer, Falk; Spanagel, Rainer; Rietschel, Marcella (Neuropsychopharmacology, 2014)
Genetic factors have as large role as environmental factors in the etiology of alcohol dependence (AD). Although genome-wide association studies (GWAS) enable systematic searches for loci not hitherto implicated in the etiology of AD, many true findings may be missed owing to correction for multiple testing. The aim of the present study was to circumvent this limitation by searching for biological system-level differences, and then following up these findings in humans and animals. Gene-set-based analysis of GWAS data from 1333 cases and 2168 controls identified 19 significantly associated gene-sets, of which 5 could be replicated in an independent sample. Clustered in these gene-sets were novel and previously identified susceptibility genes. The most frequently present gene, ie in 6 out of 19 gene-sets, was X-ray repair complementing defective repair in Chinese hamster cells 5 (XRCC5). Previous human and animal studies have implicated XRCC5 in alcohol sensitivity. This phenotype is inversely correlated with the development of AD, presumably as more alcohol is required to achieve the desired effects. In the present study, the functional role of XRCC5 in AD was further validated in animals and humans. Drosophila mutants with reduced function of Ku80—the homolog of mammalian XRCC5—due to RNAi silencing showed reduced sensitivity to ethanol. In humans with free access to intravenous ethanol self-administration in the laboratory, the maximum achieved blood alcohol concentration was influenced in an allele-dose-dependent manner by genetic variation in XRCC5. In conclusion, our convergent approach identified new candidates and generated independent evidence for the involvement of XRCC5 in alcohol dependence.